Augmented mitochondrial cytochrome c oxidase activity in children with iron deficiency: a tandem between iron and copper? - Bahadir, Aysenur (Arch Med Sci, 2016)
INTRODUCTION: Dyshomeostasis of essential trace elements including iron and copper plays a key role in the pathogenesis of a myriad of serious conditions including iron deficiency (ID) anemia, in which impaired cellular energy metabolism is prominent. Although experimental studies documented decreased activity of cytochrome c oxidase (CytOx) in ID, there are not enough clinical data. The present study was conducted to determine serum copper levels and activity of mitochondrial CytOx in isolated lymphocytes of patients with iron deficiency. MATERIAL AND METHODS: A total of 210 cases (2–17 years) were included in this prospective study. Serum iron and copper levels were measured. According to the serum iron levels, patients were allocated to iron deficient (ID, n = 70) and iron deficiency anemia (IDA, n = 70) groups, and iron-sufficient participants were allocated to the control group (n = 70). Activity of CytOx in the circulating lymphocytes was colorimetrically measured and compared with the controls. RESULTS: The CytOx activity was significantly higher in the IDA (2.9 ±1.2 mOD/min, n = 62) group compared to the control group (2.4 ±1.3 mOD/min, n = 68, p < 0.001). Interestingly, serum copper levels were significantly higher in both the ID (106.9 ±55.5 μg/dl, n = 64, p = 0.0001) and IDA (115.1 ±50.2 μg/dl, n = 59, p = 0.0001) groups than the control group (72.1 ±46.7 μg/dl, n = 69). CONCLUSIONS: Higher serum copper levels in patients with IDA implicate co-operative interaction between these trace elements. The elevated CytOx activity in patients with IDA is probably secondary to the normal/elevated serum copper levels.